Oxygen therapy in acute exacerbations of chronic obstructive pulmonary disease. (June 2015) - Pilcher, Janine; Weatherall, Mark; Perrin, Kyle; Beasley, Richard
Abstract : During the last decade, there have been major advances in knowledge of the effects of oxygen therapy in patients with acute exacerbations of chronic obstructive pulmonary disease. This includes a randomised controlled trial of oxygen therapy in the pre-hospital setting, which showed that high concentration oxygen therapy leads to a 2.4-fold increased risk of mortality compared with titrated oxygen therapy to maintain oxygen saturations (SpO2 ) within a target range of 88–92%. Professional guidelines now recommend the use of supplementary oxygen in acute exacerbations of chronic obstructive pulmonary disease only if the SpO2 is less than 88%, with titration to achieve an SpO2 of 88–92%, and the delivery of bronchodilators by air-driven nebulisation or metered dose inhaler with a spacer. The aim of this review is to provide an overview of the evidence base that underpins these recommendations. We suggest that their implementation will require important changes to current clinical practice in which there is an entrenched culture of the use of high concentration oxygen therapy.